PENGARUH INDIKATOR MEKANISME CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN PUBLIK DI INDONESIA - Ndaruningpuri Wulandari (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2006)
The early perspective corporate governance come from agency theory. In the model of agency theory, principal is ownership of the company who give their right to agent. The conflict of interest between principal and agent could be happen because existence of dissociation between ownership and management of company. The corporate governance appear to minimize that conflictand to control they behaviour. The aim of this research is to find out empirical evidence about the influence of corporate governance mechanism indicator to public company performance in Indonesia.Population of this study is company were listed in Jakarta Stock Exchange (BEJ), with amount of sampel 91 public company. There is two indicator of corporate governance mechanism in this research, first the internal corporate governance mechanism indicator was measured and proxied by the amount of board of directors, independent board of commissioner proportion, anddebt to equity. The second is external corporate governance mechanism was measured and proxied by institutional ownership. The performance of public company was measured and proxied by tobin's q. Hipotheses were tested by analysis of multiple linier regression.This study reveals that in the internal corporate governance mechanism, only debt to equity have positive significant effect to company performance. The amount of board of directors and independent board of commissioner proportion do not have positive significant effect to company performance. The institutional ownership as external corporate governance mechanism do not have positive effect significant to company performance.